Determinants of financial knowledge among adolescents - Nkomazana, Njabulo; Sibanda, Mabutho; Duve, Richard (2016)
The study measures the level of financial knowledge among the adolescents in Zimbabwe, with a particular focus on secondary school pupils. Financial knowledge is critical in providing lifelong skills and knowledge for handling personal finances beyond school. A sizeable amount of previous studies underscores the importance of financial knowledge in making sound financial decisions leading to financial growth and wealth accumulation. A descriptive crosssectional research design was employed, with data being collected from Gweru district’s ten secondary schools. The schools were spread across the three strata (secondary schools in low-density areas, secondary schools in high-density areas and secondary schools in rural areas). A self-administered questionnaire with 44 questions, adapted from the Jump$tart financial literacy survey, was employed to collect data and 763 students participated in the study. Results revealed that the average financial knowledge score was very low at 33.3%. The location of the school and student’s learning mode were the important determinants of financial knowledge among respondents. Financial knowledge did not vary by gender. It was concluded that secondary school pupils are less knowledgeable about financial decision making and this will reduce their financial prosperity. Clearly, broader environmental factors such as school location and learning mode exerted the most important influence in the accumulation of financial knowledge. The study recommends that the Ministry of Education, Sport and Culture should consider introducing a compulsory subject at the Ordinary level of study so as to equip the students with the important skill in personal finance management.